Discrete logarithm problem in matrix - Tvarijonas, Povilas; Dosinas, Gediminas Simonas; Sakalauskas, Eligijus (Lietuvos matematikos rinkinys, 2023)
In this paper the discrete logarithm problem in matrix in finite fields is formulated, possible ways of solution are given.